The theory of Maqasid al-Shari’ah-A literature review and research agenda - Abu Talib, M.M.; Noor Naemah, A.R. (Perpustakaan Negara Malaysia, 2016)
The theory of maqasid al-shari’ah refers to the higher objectives of Islamic law set out by the Lawgiver in order to ensure human welfare through achieving every possible benefit and avoiding any potential danger. It is hard to trace the precise term maqasid al-shari’ah in the literature of early Islamic legal thought. However, this absence does not necessarily mean that maqasidic approach was absent in the early period of legal thought. It rather has been keeping abreast of the developments of literature of Islamic legal thought, albeit the concept was theorized and crystallized in the later period. The concept remained the same with full reservation within the circle of few early scholars. Moreover, the contemporary studies continue focusing mainly on a few traditional aspects of the theory. Meanwhile, the development and evolution of the theory requires study of all discussions contributed to it by the pioneers to discover new insights. It also requires study of some other aspects of the maqasid theory that will contribute to the Islamic jurisprudence for the modern society. At this very point, this paper aims to present a review of the contemporary literature on the pioneers of theory of maqasid al-shari’ah and to suggest a few research directions for future developments. The paper will employ an historical and content analysis method to achieve its objective. The expected outcome of the paper is that it will serve as a base for future studies in Islamic jurisprudence.